Shared identity construction: the third space exploration - Idrus, Faizah (Centre for Promoting Ideas, USA, 2012)
Ethnic and cultural tension and conflicts have escalated in Malaysia bringing undesirable impacts on the nation’s economy and, most importantly, on inter-ethnic relationships. Thus, this study proposes the need to construct a shared Malaysian identity, starting from the classroom, which is facilitated by teachers through the use of short stories written by Malaysians. The study is grounded in the notion of hybridity in the Third Space espoused by Bhabha (1994) and ameliorated and geared towards the classroom context by the works of Gutierrez (1999, 2004, 2008). The inquiry was designed using primarily qualitative research instruments with 7 English Language teachers, and group interviews with 6 groups of students from 4 different schools in Kuala Lumpur. The findings from the analyses of the results show various attitudes, beliefs and teaching and practices in the English language classroom in response to the notion of constructing a shared identity in the Third Space